KONSTRUKSI NILAI TENGGANG RASA DALAM AL-QUR’AN DAN IMPLEMENTASINYA DALAM KOMUNIKASI DIGITAL: STUDI TAFSIR FI ZILAL AL-QUR’AN - Dita Nursafitri (LP2M STIK KENDAL, 2026)
This study examines the concept of tolerance in the digital world from the perspective of the Qur'an, focusing on Sayyid Qutb's interpretation in his Fi Zilal Al-Qur’an. Social media often presents challenges in maintaining ethical communication, such as hate speech and intolerance. The research aims to analyze the concept of tolerance as interpreted by Sayyid Qutb and its application to social media. Employing a qualitative descriptive approach, the study adopts a library research method with Fi Zilal Al-Qur'an as the primary source. The analyzed verses include Surah Al-Hujurat, Surah Al-Isra, Surah Al-Baqarah, and Surah An-Nur. The findings reveal that Sayyid Qutb's Fi Zilal Al-Qur’an emphasizes mutual respect, tolerance, polite language, and the preservation of harmony in social interactions, both in the real and digital worlds. Applying these values can foster an inclusive and harmonious social media environment. This study provides ethical guidelines relevant for social media users to uphold ethical communication in accordance with Islamic teachings.